Neuroleptic hyperprolactinemia medicamentous correction - L. N. Gorobets; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article discusses various aspects of the main approaches to the issue of correction of neuroleptic hyperprolactinemia. Based on the generalized scientific and practical experience, algorithms for corrective therapy with dopamine agonists - bromocriptine and cabergoline (Dostinex) are given. The data on indications and contraindications to prescribing therapy with these drugs are substantiated, as well as features of their side effects.